Overdose deaths and the COVID‐19 pandemic in British Columbia, Canada. (15th December 2021) - Palis, Heather; Bélair, Marc‐André; Hu, Kevin; Tu, Andrew; Buxton, Jane; Slaunwhite, Amanda
Abstract: Introduction: British Columbia (BC) declared an overdose public health emergency in 2016. Since then, BC has consistently reported the highest overdose death rates of any province in Canada. In the context of the COVID‐19 pandemic, overdose deaths in BC reached a record high in 2020. This analysis reports on changes in the profile of people who have died of overdose since BC's declaration of COVID‐19 as a public health emergency on 17 March 2020. Methods: Using BC Coroners Service data, Chi‐square tests and multivariable logistic regression were conducted to compare demographic, geographic and post‐mortem toxicology data between people who died of overdose before (17 March–31 December 2019) and after (17 March–31 December 2020) BC's declaration of COVID‐19 as a public health emergency. Results: Overdose deaths observed since 17 March 2020 ( n  = 1516) more than doubled those observed in the same period in 2019 ( n  = 744). In the adjusted logistic regression model, odds of death in the post compared to pre‐COVID‐19 period was significantly higher among males compared to females, among all older age groups compared to people aged 30–39, and was lower in public buildings compared to private residences. Discussion and Conclusions: Alongside a significant increase in overdose deaths since BC's declaration of COVID‐19 as a public health emergency, the demographic profile of people who have died of overdose has changed. Ongoing overdose prevention efforts in BC must seek to reach people who remain most isolated, including older adults, who during dual public health emergencies are facing compounded risk of preventable mortality.